Brugia malayi Glycoproteins Detected by the Filariasis Test Strip Antibody AD12.1 - Hertz, Marla I.; Hamlin, Irene; Rush, Amy; Budge, Philip J. (Frontiers in Tropical Diseases, 2021)
Background Rapid and accurate prevalence mapping of lymphatic filariasis (LF) is necessary to eliminate this disfiguring and disabling neglected tropical disease. Unfortunately, rapid tests such as the filariasis test strip (FTS) for Wuchereria bancrofti, the causative agent of LF in Africa, can cross-react with antigens circulating in some persons infected by the African eye worm, Loa loa, rendering the test unreliable in eleven co-endemic nations. The intended target of the FTS is a heavily glycosylated W. bancrofti circulating filarial antigen (Wb-CFA). Previously, we determined that the FTS monoclonal antibody, AD12.1, which detects a carbohydrate epitope on Wb-CFA, also detects multiple L. loa proteins in cross-reactive sera from persons with loiasis. Since the carbohydrate epitope recognized by AD12.1 is present on glycoproteins of other parasitic nematodes, including Brugia species, it is unclear why reactive glycoproteins are not detected in infections with other filarial parasites. Methods To gain a better understanding of the proteins recognized by the FTS diagnostic antibody, we used proteomics and lectin array technology to characterize filarial glycoproteins that are bound by the AD12.1 antibody using Brugia malayi as a model. Results Distinct but overlapping sets of AD12 glycoproteins were identified from somatic and excretory/secretory worm products. One of the identified proteins, Bm18019 was confirmed as a secreted AD12-reactive glycoprotein by in-gel proteomics and immunoassays. Based on lectin binding patterns, Brugia AD12-reactive glycoproteins express glycans including core fucose, galactose, N-acetylglucosamine and galactose(β1-3)N-acetylgalactosamine in addition to the epitope recognized by AD12.1. None of the lectins that bound B. malayi AD12 glycoproteins had affinity for the Wb-CFA, highlighting a key difference between it and other AD12 glycoproteins. Conclusions B. malayi somatic and excretory/secretory proteins are similar to L. loa antigens found in FTS-positive human sera, bolstering the hypothesis that circulating L. loa AD12 antigens result from worm tissue damage or death. The difference in glycan and protein composition between the Wb-CFA and other AD12 glycoproteins can be used to differentiate LF from cross-reactive loiasis.